Efeito de atmosfera controlada no desenvolvimento de Monilinia fructicola e na qualidade pós-colheita de pêssegos 'Aurora-1' - Fernandes, Joana Diniz Rosa [UNESP] (2014)
The objective of this research was to evaluate the influence of controlled atmosphere with different concentrations of carbon dioxide and oxygen alone in control in vitro and in vivo Monilinia fructicola; evaluating the physiological, physicochemical and biochemical behavior of peaches 'Aurora-1' when subjected to controlled atmosphere. The effect of controlled atmosphere is composed of four concentrations of CO2 (1, 3, 6 and 12% CO2 + 20% fixed concentration of O2) and four atmospheres of O2 (1, 6, 40 and 80% O2). Control fruits remained in atmosphere of 21% O2. They were stored at 12 °C and 98% RH. In vitro we evaluated the mycelial growth of Monilinia fructicola using 10 Petri dishes per treatment. The experiment in vivo was assessed by peaches 'Aurora 1' inoculated, using three replicates of five fruits each. The experiment of extending the life of peaches was evaluated using three replicates of five fruits each. The experimental design was completely randomized. In vivo experiments and in the experiment of prolonging the lifetime incidence and disease severity (lesion diameter), external appearance, accumulated loss of fresh weight, fruit firmness, pulp color and background color of the bark were analyzed , soluble solids and titratable acidity, enzymes activities of peroxidase and polyphenyloxidase, contents of soluble and total pectin. The atmosphere of 12% CO2 + 20% O2 and 6% O2 recorded the lowest Monilinia fructicola mycelial growth after 14 days of storage. The condition of the controlled atmosphere of 1% CO2 + 20% O2 and 40% O2 allowed lower mycelial growth in peaches inoculated with Monilinia fructicola. The controlled atmosphere condition with 1% CO2 + 20% O2 was adequate to allow the absence of disease during the 28 days of storage without compromising the physical-chemical characteristics of fruits. The controlled atmosphere containing 1% O2 are the best conditions for storing fruits